2024
DOI: 10.1111/codi.16925
|View full text |Cite
|
Sign up to set email alerts
|

Do risk scores improve use of faecal immunochemical testing for haemoglobin in symptomatic patients in primary care?

Jayne Digby,
Callum G. Fraser,
Gavin Clark
et al.

Abstract: AimFaecal immunochemical testing (FIT) is used in the detection of colorectal cancer (CRC). FIT is invariably used at a single faecal haemoglobin (f‐Hb) concentration threshold. The aim of this observational study was to explore risk scoring models (RSMs) with f‐Hb and other risk factors for CRC in symptomatic patients attending primary care, potentially speeding diagnosis and saving endoscopy resources.MethodRecords of patients completing FIT were linked with The Scottish Cancer Registry and with other databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The FAST score did not incorporate blood tests into the risk prediction model, instead using f-Hb level, age and sex 26 . A further study modelling the risk of CRC using logistic regression in a population in Scotland concluded no benefit to the use of a risk score in those with a low FIT test however it suggested that modelled risk might allow the raising of the current threshold and thus reduce endoscopy demand 27 . A recent systematic review of the performance of f-Hb-based risk prediction models identified 22 studies combining FIT with one or more variable to predict the risk of CRC or advanced colonic polyps 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The FAST score did not incorporate blood tests into the risk prediction model, instead using f-Hb level, age and sex 26 . A further study modelling the risk of CRC using logistic regression in a population in Scotland concluded no benefit to the use of a risk score in those with a low FIT test however it suggested that modelled risk might allow the raising of the current threshold and thus reduce endoscopy demand 27 . A recent systematic review of the performance of f-Hb-based risk prediction models identified 22 studies combining FIT with one or more variable to predict the risk of CRC or advanced colonic polyps 11 .…”
Section: Discussionmentioning
confidence: 99%